Use of the VRUT System in Education of Railway Vehicles (Current Problems in Rail Vehicles, 2025)
This text is a sequel of the author's earlier paper from the ProRail 2023 conference in Žilina, which was dedicated to the virtual reality laboratory at the Faculty of Mechanical Engineering on the CTU. The paper deals with the use of the VRUT (Virtual Reality Universal Toolkit, developed by Škoda Auto a.s.) system in teaching of rolling stock at the faculty. The contribution describes the basic properties of the system, its general use and benefits for students of the faculty.
Keywords: virtual reality; railway vehicles; VRUT; teaching